Respuesta :

Solution:

[tex]\rightarrow\sf((p(x) {x}^{2} + 2x + 4)( {x}^{2} + 2x + 4)) \\ = \sf {ax}^{2} + bx + c \\ = \sf(p(x) {x}^{2} {x}^{2} + p(x) {x}^{2} (2x) + p(x) {x}^{2} \times 4 + 2x \times {x}^{2} + 2x(2x) + 2x \times 4 + {4x}^{2} + 4(2x) + 4 \times 4) \\ = \sf( {x}^{4} p(x) + {2x}^{3} p(x) + {4x}^{2} p(x) + {2x}^{3} + {8x}^{2} + 16x + 16) \\ \rightarrow \large\boxed{\sf\red{{{x}^{4} p(x) + {2x}^{3} p(x) + {4x}^{2} p(x) + {2x}^{3} + {8x}^{2} + 16x + 16}}}[/tex]

Answer:

[tex]\large\boxed{\sf{\red{{x}^{4} p(x) + {2x}^{3} p(x) + {4x}^{2} p(x) + {2x}^{3} + {8x}^{2} + 16x + 16}}}[/tex]

[tex]\color{red}{==========================}[/tex]

✍︎ʜɴǫɴ

✍︎ʀʀʏɴʟʀɴɪɴɢ

✍︎ɪ ʀ